Prevalence and determinants of depression in geriatric women in an urban slum area of Mumbai suburbs - Srivastav, Manissha; Bavaskar, Yogita; Choudhary, Ravindra; Agrawal, S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Lifespan have increased worldwide. Increasing lifespan has brought in its wake, a host of non-communicable diseases. Worldwide, depression affects more women than men and it is also one of the morbidities amenable to treatment. Due to numerous socio-economic and cultural reasons, geriatric women in India bear the brunt of depressive ailments. Coupled with the lack of economic independence and gender disparity, this affliction and the affected both have remained in the shadows. The objective of the study was to assess the prevalence of depression and to study the association between some determinants of depression among geriatric women. Methods: A community based cross sectional study was conducted among geriatric women in an urban slum area. 336 women were included in the study. Mental health status in geriatric sample was studied by using 30 point geriatric depression scale. Results: Out of 336 total subjects, 171 (50.89%) were suffering from depression out of which 88 (26.19%) were showing mild depression and 83 (24.70%) were suffering from major depression. Marital status, unemployed status, economic dependency, lack of regular exercise, presence of addictions was found to be the risk factors for the depression. Conclusions: There was a high prevalence of depression in elderly women therefore Geriatric counseling and screening centers are to be established at health care institutes.